Effect of temperature on translocation frequency of the Tn3 element. - Kretschmer, P J (1979)
The effect of temperature on the translocation frequency of the Tn3 element was investigated. The temperature optimum for translocation of Tn3 was in the range from 26 to 30 degrees C. At temperatures above 30 degrees C, the translocation frequency decreased rapidly and linearly; at 36 degrees C it was only 5% of the frequency observed at 30 degrees C. The duration and reversibility of the temperature effect were utilized to demonstrate a requirement for protein synthesis in the translocation process.